2020
DOI: 10.3390/molecules25071625
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Antimetastatic Effects of Praeruptorin C on Human Non–Small Cell Lung Cancer through Inactivating ERK/CTSD Signalling Pathways

Abstract: Praeruptorin C (PC) reportedly has beneficial effects in terms of antiinflammation, antihypertension, and antiplatelet aggregation, and it potentially has anticancer activity. However, the effect of PC on human non–small cell lung cancer (NSCLC) is largely unknown. Compared with the effects of praeruptorin A and praeruptorin B, we observed that PC significantly suppressed cell proliferation, colony formation, wound closure, and migration and invasion of NSCLC cells. It induced cell cycle arrest in the G0/G1 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Some other studies had demonstrated that praeruptorin A could inhibit the migration and invasion of liver cancer cells, and inhibit the expression of the MMP1 gene by activating the extracellular signal-regulated kinase (ERK) signaling pathway, thereby inhibiting the movement of liver cancer cells ( Yu et al, 2020 ). Praeruptorin C had good pharmacological effects in anti-inflammatory, antihypertensive, and antiplatelet aggregation ( Liu et al, 2020 ). Studies had shown that praeruptorin C could significantly inhibit the proliferation, colony formation, wound healing, and migration of the non-small cell lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies had demonstrated that praeruptorin A could inhibit the migration and invasion of liver cancer cells, and inhibit the expression of the MMP1 gene by activating the extracellular signal-regulated kinase (ERK) signaling pathway, thereby inhibiting the movement of liver cancer cells ( Yu et al, 2020 ). Praeruptorin C had good pharmacological effects in anti-inflammatory, antihypertensive, and antiplatelet aggregation ( Liu et al, 2020 ). Studies had shown that praeruptorin C could significantly inhibit the proliferation, colony formation, wound healing, and migration of the non-small cell lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies had shown that praeruptorin C could significantly inhibit the proliferation, colony formation, wound healing, and migration of the non-small cell lung cancer cells. By inhibiting the phosphorylation of the ERK1/2 signaling pathway, it apparently reduced the expression of cathepsin D and thereby inhibited the invasion activity of the non-small cell lung cancer cells ( Liu et al, 2020 ). In addition, praeruptorin C has a good therapeutic role in improving neuroprotection such as motor and cognitive impairment in Huntington’s disease ( Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following, a novel approaches for the treatment of lung cancer should be discovered for the prevention of lung cancer especially NSCLC associated metastasis. In addition to intricate molecular progression of NSCLC, drug resistance is also are the main roots of mortality in NSCLC patients 24 . Though research found that investigation using human lung cancer model, is the best approach to recognize the vital pathways involved in human NSCLC, apart from the in vitro model and the potential therapeutic drug, such mechanistic study is yet to be limited due to ethical reason.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intricate molecular progression of NSCLC, drug resistance is also are the main roots of mortality in NSCLC patients. 24 Though research found that investigation using human lung cancer model, is the best approach to recognize the vital pathways involved in human NSCLC, apart from the in vitro model and the potential therapeutic drug, such mechanistic study is yet to be limited due to ethical reason. However, animal models offer an alternative for the exploration of the disease development.…”
mentioning
confidence: 99%
“…Epigallocatechin gallate could inhibit the migration of human uveal melanoma cells via the downregulation of ERK1/2 phosphorylation [37]. Kaempferol inhibits cell migration by targeting ERK1/2 signalling in human retinal pigment epithelial cells [38]. In addition, ERK1/2 mediates the antimetastatic activity of β-mangostin against human hepatocellular carcinoma cells [39].…”
Section: Discussionmentioning
confidence: 99%